TATA CARA PENULISAN NASKAH JURNAL CALACCITRA INSTITUT SENI INDONESIA DENPASAR - I Wayan Diana Putra; Desak Putu Yogi Antari Tirta Yasa; Gede Basuyoga Prabhawita (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2023)
Kampus Merdeka is part of the independent learning policy by the Ministry of Education. Mahatma Pictures is one of the Production Houses that focuses on creative content such as Company Profile, Advertisement, Short Movie and also documentary. The purpose of making work writing is to fulfill the final project, the MBKM program. In writing, the writer uses theoretical foundations from various sources to make a benchmark in making Feud films so as not to deviate from established rules such as Bowen and Thomson which explain the theory of dynamic cameras, Joseph V. Mascelli explained the cinematographer's theory, and Himawan pratista who explained the composition of framing, lighting, and mise en scene. In the application of dynamic camera movements, the writer uses the hand held technique to create a natural shake effect. By utilizing natural light for key light with the aim of getting the concept of natural lighting. the movement of the camera only uses hands to get a natural shake. Due to the wide movement of the camera. The application of camera movements in feud films is useful to deliver viewers to enter the atmosphere of action films